Globalızatıon and the European Unıon: Examınatıon of the European Integratıon ın the lıght of theorıes of globalızatıon - Alamese, Yahya (My University, 2016)
Dünya 1940larden beri küreselleşme olarak adlandırılan büyük, hızlı ve karmaşık bir dönüşüm yaşamaktadır. Avrupa bütünleşmesi da küreselleşme ile aynı zaman diliminde ortaya çıkmış ve gelişmiştir. Küreselleşme ve Avrupa bütünleşmesi arasındaki ilişki her iki süreci ve bugünün ve geleceğin dünyasını anlamak için çok önemlidir. Avrupa bütünleşmesi açısından küreselleşme özellikle de ekonomik küreselleşme genellikle dışsal bir hızlandırıcı olarak anlaşılmaktadır. Bu görüş bazı açılardan doğru olmakla birlikte gerçeğin tamamını yansıtmamaktadır. Küreselleşme süreci sosyal, politik, kültürel, teknolojik ve çevresel boyutları içermekte ve bu boyutlar da Avrupa bütünleşmesini etkilemektedir. Diğer yandan, Avrupa bütünleşmesi da küreselleşme üzerinde çeşitli etkilerde bulunmaktadır. İlave olarak, Avrupa Birliği Avrupa sosyal modelinin neoliberal küreselleşmeye bir alternatif sunduğunu iddia etmektedir. Sonuçta küreselleşme ve Avrupa bütünleşmesi arasındaki ilişki göründüğünden daha karmaşıktır ve bu alanda daha kapsamlı açıklamalara ihtiyaç bulunmaktadır. Bu tezin amacı küreselleşme ve Avrupa bütünleşmesi arasındaki ilişkiyi küreselleşme teorileri ışığında inceleyerek Avrupa bütünleşmesini anlamak için alternatif bir perspektif sunmaktır.

The world has experienced huge, rapid and complex transformation, which is called globalization, since 1940s. The European integration process has emerged and progressed during the same period with globalization as well. The relationship between globalization and the European integration is significant to understand the two processes together with today's and tomorrow's world. Globalization, notably economic globalization, is usually perceived as an exogenous accelerator for the European integration. Although this argument is true to a certain extent, it does not comprise all parts of the reality. The globalization process has social, political, cultural, technological and environmental dimensions and they have affected the European integration as well. On the other hand, the European integration has also certain impacts on the globalization process. Furthermore, European Union claims that European social model provides an alternative form of globalization rather than neoliberal globalization. Consequently, the relationship between the globalization process and European integration process is more complex than it seems and explanations that are more comprehensive are needed in this area. The aim of this thesis is to examine the relationship between the European integration and globalization in the light of globalization theories to provide an alternative perspective to understand the European integration.
Keywords: Avrupa Birliği; Siyasi açıdan; Uluslararası ilişkiler